2021
DOI: 10.3390/foods10061237
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Hedonic Responses, Facial Expressions and Self-Reported Emotions of Consumers Using Commercial Yogurts: A Cross-Cultural Study

Abstract: Hedonic scale testing is a well-accepted methodology for assessing consumer perceptions but is compromised by variation in voluntary responses between cultures. Check-all-that-apply (CATA) methods using emotion terms or emojis and facial expression recognition (FER) are emerging as more powerful tools for consumer sensory testing as they may offer improved assessment of voluntary and involuntary responses, respectively. Therefore, this experiment compared traditional hedonic scale responses for overall liking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
(73 reference statements)
1
12
0
1
Order By: Relevance
“…On the contrary, coconut yogurts were associated with "firm", "sour", and "astringent", which had a negative association with the overall liking. These findings confirm that textural and mouthfeel properties can have a significant effect on the acceptability of yogurt products [41].…”
Section: Attribute Terms and Emotional Responses Of Yogurtssupporting
confidence: 83%
“…On the contrary, coconut yogurts were associated with "firm", "sour", and "astringent", which had a negative association with the overall liking. These findings confirm that textural and mouthfeel properties can have a significant effect on the acceptability of yogurt products [41].…”
Section: Attribute Terms and Emotional Responses Of Yogurtssupporting
confidence: 83%
“…Prior work showed that the interpretation of emoji varies (Miller et al, 2016;Kimura-Thollander and Kumar, 2019), also between cultures (Guntuku et al, 2019;Gupta et al, 2021). Even within the same culture, ambiguity and double meanings of emoji exist (Reelfs et al, 2020) and differences exists on the basis of an individual usage (Wiseman and Gould, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Not all emoji have a universally agreed on meaning. Prior work showed that differences in the meaning of emoji exist between cultures (Guntuku et al, 2019;Gupta et al, 2021). Even within the same culture, ambiguity and double meanings of emoji exist (Reelfs et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationships between primary sensations such as flavor, taste, and texture, and higher-level sensations or judgments such as freshness and richness of tastes when eating food products is essential for determining the food values. Relationships between primary sensations and higher-level human responses, including emotions, have been intensively researched using static sensory evaluation methods [9][10][11][12][13][14][15][16]. For example, in [10], primary sensations such as tastes and mouth feels of several vegetables and fruits were linked with higher-level of attributes such as summery, refreshing, and fresh-made.…”
Section: Introductionmentioning
confidence: 99%